DOI: 10.11606/d.18.2006.tde-25072006-150218
|View full text |Cite
|
Sign up to set email alerts
|

Estudos ecológicos e ecotoxicológicos de Melanoides tuberculata Müller, 1774 (Gastropoda, Thiaridae), espécie exótica para a região neotropical

Abstract: Ao CNPq pela concessão da bolsa de mestrado. À Renata, que muito me ensinou e com quem foi maravilhoso ter convivido num clima de amizade e cooperação. À amiga e colega de tantas provações e dificuldades que tornou essa fase mais fácil e muito mais divertida. Obrigada, Fer. À Emanuela e Mariana pelo auxílio no laboratório e pelos momentos de descontração. À Edna e Malu pela boa vontade e carinho com que sempre agiram, quando solicitadas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Maximum temperatures of 30.9 °C were recorded, and the minimum measured was 27.5 °C. observed that M. tuberculatus survives well in temperatures between 18 and 32 °C, and a recent study by Okumura (2006) showed that, in the laboratory, the range of tolerance of this species is between 16 and 37 °C, with an optimum range between 29 and 34 °C. This reinforces the plasticity of this species, which is capable of occupying environments in extreme situations, and is highly competitive.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Maximum temperatures of 30.9 °C were recorded, and the minimum measured was 27.5 °C. observed that M. tuberculatus survives well in temperatures between 18 and 32 °C, and a recent study by Okumura (2006) showed that, in the laboratory, the range of tolerance of this species is between 16 and 37 °C, with an optimum range between 29 and 34 °C. This reinforces the plasticity of this species, which is capable of occupying environments in extreme situations, and is highly competitive.…”
Section: Discussionmentioning
confidence: 87%
“…M. tuberculatus can reproduce sexually, but reproduces mainly via parthenogenesis, which partly accounts for its success as an invasive organism; it is viviparous. According to Dudgeon (1986), individual snails as small as 0.28 cm can be reproductively mature, although Okumura (2006) observed, in the laboratory, individuals of about 1.0 cm long in their first reproduc- tion. Therefore we assume that most of the individuals found were mature.…”
Section: Discussionmentioning
confidence: 99%
“…Isto porque por ser uma espécie altamente invasiva, uma característica marcante é sua capacidade de colonizar áreas impactadas por atividades antrópicas, principalmente locais de águas rasas, com substrato de granulometria fina e rico em detritos orgânicos (Martins-Silva e Barros, 2001;Okumura, 2006). Estudos realizados por Kock e Wolmarans (2009) também relacionaram a abundância de M. tuberculata em ambientes com substratos lamacentos ou arenosos e em temperaturas de 25°C em média.…”
Section: Resultsunclassified
“…O fluxo natural das águas auxilia na dispersão dos organismos invasores em sistemas aquáticos (Okumura, 2006). Por isso, os ambientes de água doce estão altamente sujeitos às invasões de organismos exóticos já que apresentam grande facilidade para a dispersão pelo próprio fluxo d´água (Welcomme, 1988).…”
Section: Introductionunclassified